2012
DOI: 10.1242/jeb.068122
|View full text |Cite
|
Sign up to set email alerts
|

Spectral tuning by selective chromophore uptake in rods and cones of eight populations of nine-spined stickleback (Pungitius pungitius)

Abstract: SUMMARYThe visual pigments of rods and cones were studied in eight Fennoscandian populations of nine-spined stickleback (Pungitius pungitius). The wavelength of maximum absorbance of the rod pigment ( max ) varied between populations from 504 to 530nm. Gene sequencing showed that the rod opsins of all populations were identical in amino acid composition, implying that the differences were due to varying proportions of chromophores A1 and A2. Four spectral classes of cones were found (two Scones, M-cones and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 76 publications
2
29
0
Order By: Relevance
“…Such variation in chromophore use is in line with that found in a related species, the nine-spined stickleback (Pungitus pungitus), where the absorbance of all visual pigments (except S) could be accounted for by chromophore shifts (Saarinen et al, 2012). It therefore appears that, in both stickleback species, chromophore use varies between photoreceptor types and multiple SWS2 opsins may be expressed within the single cone population.…”
Section: Visual Pigments and Opsin Sequencessupporting
confidence: 80%
“…Such variation in chromophore use is in line with that found in a related species, the nine-spined stickleback (Pungitus pungitus), where the absorbance of all visual pigments (except S) could be accounted for by chromophore shifts (Saarinen et al, 2012). It therefore appears that, in both stickleback species, chromophore use varies between photoreceptor types and multiple SWS2 opsins may be expressed within the single cone population.…”
Section: Visual Pigments and Opsin Sequencessupporting
confidence: 80%
“…Overall, the sample sizes (numbers of individuals) for determining rod spectra for each condition (e.g. time point) in the present study are typical and sufficient for visual pigment studies (Jokela-Määttä et al, 2007;Saarinen et al, 2012), as suggested also by the relatively small standard deviations.…”
Section: Arctic Charr and Whitefish: Different Adaptations For High Vmentioning
confidence: 66%
“…The sample sizes for each morph and season are typical or even slightly higher compared to many visual pigment studies (e.g. Jokela-Määttä et al, 2007;Saarinen et al, 2012). We acknowledge that a higher number of samples and sampling times would have been necessary to focus more on cone pigments and potentially reveal more insights to A1:A2 ratio along fish ontogeny.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations